Determinants of welfare benefit use of immigrant groups - longitudinal evidence from Germany - Frank, Emily (Frontiers in Sociology, 2022)
While recent literature in Germany has compared predictors of welfare use between EU and non-EU immigrants, refugees have yet to be added to the analysis. Using survey data of approximately 4,000 immigrants living in Germany, I examine the determinants of basic unemployment benefits receipt for intra-EU immigrants, refugees, and third country immigrants. In particular, I investigate how education affects the likelihood of welfare use for each immigrant group. Even after controlling for human capital factors, sociodemographic characteristics, and factors related to migration such as legal status and age at migration, refugees remain significantly more likely to receive benefits. Results demonstrate that higher education significantly decreases the likelihood of welfare receipt for EU and third country immigrants, but much less so for refugees. These findings may indicate that refugees’ education is not being used to its full potential in the labor market or that they face additional challenges hindering their labor market integration. A further and unanticipated finding is that immigrants who hold permanent residency or German citizenship are less likely to receive unemployment benefits, pointing either to positive effects of a secure residency or selection into permanent residency and citizenship among those with the greatest labor market success. Overall, this research shows that challenges beyond human capital deficiencies and sociodemographic characteristics must be considered when studying immigrants’ receipt of social benefits, that not all educational credentials are valued equally, and that the experiences of refugees differ in significant ways from those of other immigrant groups.